A review of potential neuropathological changes associated with ketamine. Issue 6 (3rd June 2022) - Nogo, Danica; Nazal, Hana; Song, Yuetong; Teopiz, Kayla M.; Ho, Roger; McIntyre, Roger S.; Lui, Leanna M.W.; Rosenblat, Joshua D.
ABSTRACT: Introduction: Ketamine is an established intervention for treatment-resistant depression (TRD). However, long-term adverse effects with repeated doses remain insufficiently characterized. Although several animal models have shown N-methyl-D-aspartate glutamate receptor antagonists to produce various neuropathological reactions, attention surrounding the risk of brain lesions has been minimal. Areas covered: The current review focuses on potential neuropathological changes associated with ketamine. Search terms included variations of ketamine, Olney lesions, tau hyperphosphorylation, and parvalbumin interneurons. Expert opinion: Daily high-dose ketamine use in substance use disorder (SUD) populations was associated with clear neurotoxic effects, while no studies specifically evaluated effects of ketamine protocols used for TRD. It is difficult to discern effects directly attributable to ketamine due to methodological factors, such as comorbidities and dramatic differences in dose in SUD populations versus infrequent sub-anesthetic doses typically prescribed for TRD. Taken together, animal models and human ketamine SUD populations suggest potential neuropathology with chronic high-dose ketamine exposure exceeding those recommended for adults with TRD. It is unknown whether repeat sub-anesthetic dosing of ketamine in adults with TRD is associated with Olney lesions or other neuropathologies. In the interim, practitioners should be vigilant for this possibility recognizing that the condition itself is associated with neurodegenerative processes.